Uncovered bargaining solutions - Michele Lombardi; Marco Mariotti (Queen Mary University of London, Department of Economics, 2007)
An uncovered bargaining solution is a bargaining solution for which there exists a complete and strict relation (tournament) such that, for each feasible set, the bargaining solution set coincides with the uncovered set of the tournament. We provide a characterization of a class of uncovered bargaining solutions.
Keywords: C72; D44; 330; Bargaining; Tournaments; Uncovered set; Non-convex problems; Verhandlungstheorie; Nichtkooperatives Spiel; Auktionstheorie